A REVIEW OF MENTAL ILLNESS AMONG ADOLESCENTS IN MALAYSIA - Wirawani Kamarulzaman; Khairul Hamimah Mohammad Jodi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The number of mental illness issues among Malaysian adolescents has increased which leads to the necessity for further exploration of its factors. Thus, the purpose of the study is to review the cases of mental illness issues among adolescents in Malaysia and the factors that lead to such issues, as well as their signs and symptoms. The qualitative design is employed with document research method. Data on the factors and numbers of cases of teenagers’ mental health issues from journal articles, books, newspapers, and other relevant sources are analysed through a thematic and comparative approach. It was found that between 2014 and 2015, a total of 3073 cases were reported which lead to depressions. Adolescents are also found to be involved in a number of illegal and aggressive activities such as drug addictions, gambling, and damaging of property due to their mental volatility. Previous research indicated that a major factor that elicits mental illness is severe psychological trauma that a person suffered as a child due to abuse. A few recommendations are also included at the end of the paper.